Hydraulic jumps and steps: the relationship between jump location and sequent depth ratio using a step - Fowler, Nicholas Thomas Stephen (My University, 2020)
Abrupt steps used in stilling basins to dissipate energy are simple and effective structures, yet certain design aspects have been neglected. A series of small-scale laboratory experiments were conducted to investigate the effect of the position of the hydraulic jump and the effect of hysteresis on step design. Five new relationships were developed for relating the jump location to the step height and the upstream and downstream flow conditions. The findings show that the position of the jump influences the design, in addition to the significant benefit of physically quantifying the position of the jump. Furthermore, a sweep-out limitation was developed from the abrupt step testing, which has potential design implications. Lastly, the hysteresis effect on both abrupt and sloping steps was expanded, providing introductory influences on the sequent depths of the hydraulic jump and the position of the jump. The study provides introductory knowledge to the significance of the position of the hydraulic jump in the design, while expanding on established hysteric knowledge for steps
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020